Perbedaan Kinerja Auditor Dilihat dari Segi Gender (Studi Empiris pada KAP di Jawa Timur) - Sri Trisnaningsih (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to empirically analyze the difference of performance of male and female auditors at public accounting firm. The performance is measured using organizational commitment, professional commitment, motivation, career opportunity and job satisfaction. The result of this research is expected to give the contribution in theory development. It is also expected to give practical contribution to the organizations, especially the public accounting firm.Subjects in this research are auditors at public accounting firm in East Java. Data were collected using survey method. The sample is selected using purposive sampling method. From 260 questionnaires disseminated to all respondents, only 105 questionnaires were returned. However, only 85 of the returned questionnaires were valid for analyses.  Independent sample t Test was used to test the hypothesis.The results prove that there is no difference of organizational commitment, professional commitment, motivation and career opportunity among male and female auditors at public accountant offices. While for the job satisfaction, the results indicate there is a difference among male and female auditors.